Analysis Of Drug Distribution System In Hospital Hospital Karanganyar - Waode Suiyati; Sunarto S (CV. Inara, 2022)
Inpatient drug services start from prescribing to patients, using drugs during treatment, until the patient returns home, there may be replacements, additional drugs and residual drugs. Although this service process is the responsibility of pharmacists, it is closely related to the role of medical personnel, nurses and the administrative division in hospitals. Research objectives Identify the percentagecompatibility between drugs and stock cards,IdentifyTurnover ratio,Identifypercentage of expired/damaged drug value,Identifythe average time used to serve prescriptions to the hands of patients,Identifypercentage of drugs served at the Karanganyar District Hospital.This research was conducted by following a descriptive research design to analyze the drug distribution system in the Inpatient Hospital of Karanganyar Regency. The data obtained in the form of primary data and secondary data. The research results arePercentage of matches between drugs and card stockis 86.6% with the indicator set is 100% it can be said to have not been effective when compared to indicators,Turn over ratio valueis 9 times turnover, the standard indicator is 8-12x capital turnover in 1 year. This means that the TOR is effective,Percentage of expired/damaged drug valueis 4.5% and the standard indicator of 0% means that it can be said to be ineffective, The average time used to serve prescriptions to the hands of patientsThe long waiting time for compound drugs is in stage II, which is 36.28 minutes, and the waiting time for non-concoction drugs is in stage II, which is 29.42 minutes, with service hours at 14.00-20.00. This is not efficient when compared to the standard value of compound drugs < 30 minutes and non-concoction drugs 15 minutes.The percentage of drugs not served is0.0085% it has not been effective with an indicator of 0%.